Survei Penggunaan Pupur Bangkal Cap Galuh Licin sebagai Kosmetik Tradisional Khas Banjarmasin - Apriani, Dini; Lutfiati, Dewi (Journal of Beauty and Cosmetology (JBC), 2021)
Pupur bangkal is a facial skin care product made from natural ingredients and has been used by women in Banjarmasin. Pupur bangkal is a culture and characteristic of the Banjar people. This study aims to determine: 1) The process of making pupur bangkal. 2) How to use and benefit from the powdered root. 3) Analyzing consumer buying interest in traditional cosmetics, powdered ginger, in the era of modern cosmetics. This type of research is descriptive including quantitative and qualitative research with the object of consumer buying interest in traditional cosmetics powder bangkal. Data collection methods used were questionnaires, interviews, and observations. Data were obtained from 30 respondents in 5 cosmetic shops. The data analysis used was descriptive statistical data analysis in the form of percentages. The results showed that 1) The process of making traditional masks is very easy to practice at home because it uses simple equipment and materials that are easily available in traditional markets. 2) Regular use of cold powder products has benefits, namely the face that looks brighter, dries up, heals acne, shrinks pores, and makes facial skin smoother and can absorb excess oil. 3) Factors that influence consumer buying interest, namely product quality factor of 50%, price affordability factor of 40% and testimonials of 10% and the results of the age of women using puppets are 17% adolescents and 83% adults. The results showed that the product quality factor of Cap Galuh Banjar powdered powder was more attractive to women aged 40 years and over.Keywords: powder bangkal, traditional cosmetics, consumer interest.